Seleksi Ikan Berbasis Penanda DNA (DNA Marker): Literature Review - Harahap, Antoni; Haser, Teuku Fadlon; Febri, Suri Purnama; Darsiani, Darsiani (Fakultas Pertanian Universitas Samudra, 2022)
Selection of fish based on DNA markers is a method or technique that has started to develop rapidly in the field of genetics and fish breeding. Selection based on DNA markers utilizes the genetic information contained in fish DNA to obtain individuals with characteristics appropriate to the stages and production of aquaculture in a timely, efficient, and measurable manner. This literature review presents several discussions and literature sources that are quite relevant regarding various aspects of DNA marker-based fish selection, including the basic principles, analytical methods, benefits, and challenges based on DNA markers, and discusses how the most recent developments in the use of methods in the process of genetic breeding and fish selection, as well as the potential for future applications.